SELECTIVE PRECIPITATION OF IMPURITIES FROM NICKEL LEACH LIQUORS - Marcelline, Stacy
Nickel is a metal which is widely used for everyday uses such as steel alloy, coin, and cooking wares because of its’ resistance to corrosion. There are two types of nickel ore in this world, laterite nickel ore and sulfide nickel ore. Sulfide nickel ore are mainly found on subtropic area while laterite nickel ore are mainly available in the equatorial countries such as Indonesia. In Indonesia, the technology to process laterite nickel ore have been developed through many leaching process, one of them being the extraction of nickel using dissolved SO2- air. The resulting liquors still possess lots of impurities in the form of metal ions. Therefore, the objectives of this study is to separate the impurities from nickel leach liquor and obtain mixed hydroxide precipitate (MHP) as the final product. Mixed hydroxide precipitate is a combination of Ni(OH)2 and Co(OH)2. Separation is done through multistage selective precipitation on artifical nickel liquors which contains Fe, Mg, Co, and Ni metals. The selective precipitation condition are varied at 25oC, 50oC, and 80oC. Precipitation procedures are equipped with aeration for 24 hours under standard room condition to ensure that all Fe(II) ions are oxidized to Fe(III) ions. Product characterization were analyzed using AAS, XRF, SEM-EDS, and XRD methods. At the second stage, 1 gr NiO is added as a seeding agent to help accelerate the heteregoneous nucleation of MHP. The highest recover of Ni(OH)2 and Co(OH)2 are obtained under temperature 50oC and 25oC on pH 9-10 that is 52,66% and 99,94%. The maximum selectivity of Ni/Fe and Co/Fe are 17,17 and 4,01 under 50oC and 25oC condition.